Description and phylogeny of a new prostomatid, Metacystis similis nov. spec. (Protista, Ciliophora) from the East China Sea - Zhang, Xiumei; Ji, Daode; Zhang, Qianqian; Li, Chenghua (Zootaxa, 2015)
The living morphology and infraciliature of a new marine prostomatid, Metacystis similis nov. spec., have been observed and investigated. Based on both morphological and molecular biological data, several closely-related and easily confused taxa were compared. The diagnosis for this new taxon: cylindrical marine Metacystis with a slightly blunt anterior end, in vivo 50–70 x 18–23 μm; body not loricate, uniformly cinctured by 16–18 transverse rings of cilia, which are also arranged in 32–36 longitudinal kineties; oral apparatus consisting of one circumoral dikinety and six girdles of densely packed monokinetids; single spherical macronucleus located in the center of the body; caudal region possessing one transparent, protruding hemicycle terminal vacuole. Information concerning the small-subunit rRNA gene sequence of the new species was also provided.